IN VITRO MULTIPLICATION OF BRUNSVIGIA UNDULATA FROM TWIN SCALE EXPLANTS - Rice, L.; Finnie, J.; Van Staden, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Brunsvigia undulata F.M.Leight. (Amaryllidaceae) is one of the many South African medicinal plants threatened by over-collection and in particular habitat loss. Micropropagation is a technique that can potentially provide a means of supplying plants for the traditional medicinal plant trade. This would decrease the pressure on wild populations and help to conserve this species. For in vitro propagation, twin scales provided a successful explant for bulblet formation. The effect of photoperiod and different combinations of plant growth regulators (e.g. naphthalene-acetic acid [NAA] and benzyladenine [BA]) on bulblet formation was investigated. Further experiments to observe the effects of photoperiod, temperature, activated charcoal, cytokinin concentrations, media type and explant size, on bulblet multiplication were also carried out. Bulblets formed readily from twin scale explants on all but one of the plant growth regulator treatments. Cytokinin concentration did not significantly effect the in vitro multiplication of half-bulblets, while whole bulblets readily multiplied to produce up to 13 bulblets from one parent bulblet.